Visualization of bleeding site on 24-hour imaging in lower gastrointestinal bleeding with 99mTc-nanocolloid: A case report - Alyani, Hilmi; Budiawan, Hendra; Nugrahadi, Trias (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Gastrointestinal bleeding can be diagnosed by history taking, physical examination, and diagnostic examinations. However, localization of gastrointestinal bleeding via a nuclear medicine examination can indicate an accurate examination to detect the location of bleeding. Radiopharmaceuticals can be selected according to a patient’s condition. Good image results are needed so that the results are conclusive and lead to further examination and management. A 2-years-old girl patient was hospitalized in a paediatric ward due to a large number of loose stools mixed with fresh blood for months after experiencing diarrhoea. The patient was active, absence any decreased appetite, pain, activity disturbances, or significant weight loss . Her parents took her for treatment to several hospitals but no improvement. The patient was referred to the Nuclear Medicine Department to undergo localization of gastrointestinal bleeding study. 99mTc-nanocolloid was injected as radiopharmaceuticals, followed by a dynamic and serial static imaging after 30 minutes. No focus of radioactivity extravasation was found. Examination was continued at 1, 2, and 24 hours. Diffuse radioactivity extravasation was found in the descending colon 24 hours after injection of the radiopharmaceutical, and she was confirmed by colonoscopy and biopsy a week later. 99mTc-labeled colloid had not been used after a few studies showed that 99mTc-red blood cell (RBC) in vitro was better at localizing gastrointestinal bleeding. Usually, 99mTc-labeled colloid remains in circulation for only 30 minutes due to rapid distribution to the reticuloendothelial system. The visualization of the bleeding site on 24-hour imaging was unusual. However, these findings suggest that 99mTc-labeled colloid can still be used with due regard to the patient's clinical active bleeding and imaging techniques.